Controlling tosylation versus chlorination during end group modification of PCL. (5th November 2022) - Beeren, Ivo A.O.; Dijkstra, Pieter J.; Massonnet, Philippe; Camarero-Espinosa, Sandra; Baker, Matthew B.; Moroni, Lorenzo
Graphical abstract: Abstract: Synthetic biodegradable materials are commonly used to create constructs for medical devices and tissue engineered constructs. However, many of the homopolymers used in FDA approved devices such as poly(ε-caprolactone) (PCL), poly(lactic acid), or poly(carbonates) lack biogically relevant functional groups to steer biological responses in a controlled fashion. Commonly, an interconversion of the end groups is required to insert addressable moieties for the attachment of biologically active groups. In this study, the activation of the hydroxyl groups of a low molecular weight PCL-diol to the corresponding p-toluene sulfonate ester using p-toluenesulfonyl chloride was performed in both dichloromethane (DCM) and dimethylformamide (DMF). To our initial surprise, we only yielded the chlorinated product in DMF, while in DCM the tosylate ester was obtained. In a small series of reactions, we studied the solvent dependent switchability between tosylation and chlorination on PCL. We concluded that in polar aprotic solvents (DMF and dimethylsulfoxide), we rapidly and efficiently converted the hydroxyl into the chloride group, whereas in inert solvents (DCM and chloroform) we yielded the tosylated product. The data suggested that solvation effects of the polar aprotic solvents led to a Sn 2 reaction of the tosyl group by the chloride. Furthermore, we utilized a polyethylene glycol (PEG) polymer to show translatability of the chlorination reaction to other (biomedical) polymers. This work highlights a new reaction pathway during the tosylation of a polymer end group, and presents a new useful strategy to insert clickable groups on synthetic polymers that are only soluble in polar aprotic solvents.